2012
DOI: 10.2343/geochemj.1.0158
|View full text |Cite
|
Sign up to set email alerts
|

The molybdenum isotopic composition of the modern ocean

Abstract: Wang et al., 2011 (1) and is converted to δ 97/95 Mo by multiplying 0.67 when the system follows mass-dependent fractionation. Though no commonly-used Mo isotopic standard currently exists (see later), the standards used by different laboratories do appear to be isotopically similar at the level of 0.1-0.2‰. Continental rock samples, such as granite, basalt, and clastic sediments, have δ 98/95 Mo of ~0.1‰ Siebert et al., 2003). Ferromanganese oxides, which scavenge Mo from seawater in oxic conditions, have a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
80
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(86 citation statements)
references
References 50 publications
3
80
1
2
Order By: Relevance
“…The alternative is that Mo was incorporated from seawater, in which dissolved Mo is predominantly in the tetrahedrally coordinated oxyanion MoO 4 2 − (Byrne, 2002) and has a nominally homogeneous δ 98/95 Mo value of~2.1‰ (Barling et al, 2001;Siebert et al, 2003;Nakagawa et al, 2012;Goldberg et al, 2013). If most of the Mo in the sample was adsorbed from seawater, we would expect a δ 98/95 Mo value of approximately −0.6‰, which is in good agreement with our results (Fig.…”
Section: Origin Of Mo In the Hydrothermal Mn Crust Samplesupporting
confidence: 90%
See 2 more Smart Citations
“…The alternative is that Mo was incorporated from seawater, in which dissolved Mo is predominantly in the tetrahedrally coordinated oxyanion MoO 4 2 − (Byrne, 2002) and has a nominally homogeneous δ 98/95 Mo value of~2.1‰ (Barling et al, 2001;Siebert et al, 2003;Nakagawa et al, 2012;Goldberg et al, 2013). If most of the Mo in the sample was adsorbed from seawater, we would expect a δ 98/95 Mo value of approximately −0.6‰, which is in good agreement with our results (Fig.…”
Section: Origin Of Mo In the Hydrothermal Mn Crust Samplesupporting
confidence: 90%
“…The striped area shows the range of Os isotopic compositions in hydrothermal fluids ( 187 Os/ 188 Os = 0.11-0.40) (Sharma et al, 2000). (Barling et al, 2001;Siebert et al, 2003;Nakagawa et al, 2012;Goldberg et al, 2013). The dashed line show the Mo isotopic compositions in hydrothermal fluids from the low-temperature ridge-flank hydrothermal system in the Cascadia Basin (δ 98/95 Mo =~0.5) (McManus et al, 2002).…”
Section: Genesis Of the Mn Crust Samplementioning
confidence: 97%
See 1 more Smart Citation
“…In such cases, authigenic Mo is typically ~1‰ lighter than the associated seawater (Arnold et al., ; Barling et al., ; Neubert, Nägler, & Böttcher, ; Poulson Brucker et al., ; Poulson, Siebert, McManus, & Berelson, ; Siebert, McManus, Bice, Poulson, & Berelson, ). In the modern ocean, the isotopic composition of Mo is about +2.3‰ (Barling et al., ; Nägler et al., ; Nakagawa et al., ; Siebert et al., ), which is significantly heavier than the riverine input of +0.7‰ (Archer & Vance, ). This disparity is maintained through dominance by the Mn oxide sink in today's well‐ventilated oceans, exporting large amounts of the lighter 95 Mo.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy and longterm reproducibility were further evaluated by analysing seawater samples from the Atlantic Ocean over a period of 2 years (Table 1, Figure 2). Previous studies showed that the d 98/95 Mo of modern open-ocean water accounts for some of the variation, and reflect a small inherent heterogeneity within ± 0.10‰ (2s) (Siebert et al 2003, Greber et al 2012, Nakagawa et al 2012, Goldberg et al 2013. Greber et al (2012) renormalised their Mo isotope data for seawater to NIST SRM 3134 = 0‰ and obtained a value of 2.09 ± 0.07‰ (2s, n = 5).…”
Section: Procedures Validationmentioning
confidence: 99%